Strategies for Tracking Immune Surveillance of Tumor Milieu during Angiogenesis: Life Sciences-Biotechnology - Praveen Kumar Vemuri; Greeshma Nimmagadda; Sreedhar Bodiga; Vijaya Lakshmi Bodiga; Suryanarayana Veeravilli; KRS Sambasiva Rao (International Journal of Life Science and Pharma Research, 2022)
Cancer is a multi-stage, multi-mechanistic, multifactorial complex process that has excessive potential for excessive proliferation with no relation to the physiological organ. Inherited genetic inclinations contribute extensively to about 10 % of breast cancers and about 13 % of colon cancers incidences. In the industrialized countries, 7% of most cancer deaths result from viral infections; 4% from occupational hazards; 2% from sunlight; 2% from air, water, and soil pollution; and less than 1% from diet and lifestyle. Formation of new blood vessels, angiogenesis, is elicited by tissue hypoxia and is essential for normal course of development of every tissue and organ. Angiogenesis unequivocally promotes tumor growth and metastasis. Tumors exhibit different rates of pathological angiogenesis and involve not only abnormally proliferating cancer cells, but also various tumor- infiltrating leukocytes and stromal cells. Local milieu of the cancers polarizes the leukocytes to support the tumor growth further. Although conventional knowledge reveals that immune surveillance helps to suppress tumor development, unresolved immune mechanisms including chronic inflammation can promote growth and progression of tumors. In this review, we outline the immune cells and their derived factors, including immunosuppressive and inflammatory cytokines that either can promote or inhibit cancer development, and the role of tumor microenvironment in this process of regulation. In the present review, the role of T-lymphocytese, NK cells, antibody dependent cell cytotoxicity, tumor escape mechanisms are presented.